2004
DOI: 10.1099/jmm.0.45568-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leptospiral immunoglobulin-like protein by Leptospira interrogans and evaluation of its diagnostic potential in a kinetic ELISA

Abstract: The search for novel antigens suitable for improved vaccines and diagnostic reagents against leptospirosis led to the identification of LigA and LigB. LigA and LigB expression were not detectable at the translation level but were detectable at the transcription level in leptospires grown in vitro. Lig genes were present in pathogenic serovars of Leptospira, but not in non-pathogenic Leptospira biflexa. The conserved and variable regions of LigA and LigB (Con, VarA and VarB) were cloned, expressed and purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 31 publications
(23 reference statements)
4
83
0
8
Order By: Relevance
“…Initial studies found that acute leptospirosis produces robust antibody responses to Lig proteins (28,39), albeit these evaluations were performed with small numbers of patient samples. Palaniappan et al found that levels of antibodies to recombinant Lig fragments as detected by ELISA correlated with MAT titers in dogs (46). However, this study did not specifically determine the performance of the assay in diagnosing acute leptospirosis in these animals.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Initial studies found that acute leptospirosis produces robust antibody responses to Lig proteins (28,39), albeit these evaluations were performed with small numbers of patient samples. Palaniappan et al found that levels of antibodies to recombinant Lig fragments as detected by ELISA correlated with MAT titers in dogs (46). However, this study did not specifically determine the performance of the assay in diagnosing acute leptospirosis in these animals.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, they are expressed in virulent strains but not in strains that have been attenuated by culture passaging (39). Lig proteins are expressed during host infection (39) and appear to induce strong antibody responses in patients (28,39) and infected animals (28,46,47). However, previous studies were performed with limited numbers of leptospirosis patients (28,39).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Lsa44 and Lsa45 share serum recognition properties with the adhesins described elsewhere, LipL32 (Flannery et al, 2001;Xu et al, 2008), LigA and LigB proteins (Palaniappan et al, 2004;Srimanote et al, 2008), Lsa27 (Longhi et al, 2009), Lsa63 (Vieira et al, 2010a), Lsa66 (Oliveira et al, 2011), and OmpL37 (Pinne et al, 2010), which have shown positive reactivity with serum samples from patients diagnosed with leptospirosis. Protein recognition by serum (1), or lsPBS containing PBS-(2), Lsa44-(3) or Lsa45-injected mouse serum (4), at a dilution of 1 : 100.…”
Section: Discussionmentioning
confidence: 99%